Cultivated Pastures Affect Nutrient Intake and Feeding Behavior of Sheep - J. V. Emerenciano Neto; G. S. Difante; H. R. Medeiros; E. M. Aguiar; L. S. Fernandes; T. F. M. Trindade; M. G. S. Bezerra; H. C. B. Oliveira; R. C. P. Galvão (Faculty of Animal Science, Bogor Agricultural University, 2020)
Cultivated pastures may increase the meat production of sheep, but it is necessary to understand the plant-animal relationships in a pastoral environment. This study aimed to assess the effect of forage cultivars on the intake and feeding behavior of sheep. Four treatments were evaluated, consisted of the cultivars Panicum maximum cvs. Aruana and Massai and Brachiaria brizantha cvs. Marandu and Piatã. Twenty-four sheep, male of the Santa Inês genotype, were used with six replications per treatment. Daily forage and nutrient intakes were evaluated in addition to time in grazing, rumination, and leisure activities. The animals in the pasture of Aruana grass demanded the most extended times of grazing and rumination (p<0.05). The leisure time was higher (p<0.05) in the animals kept in pastures of Piatã grass. The highest intakes of dry matter and crude protein in g/day (p<0.05) were found in the animals kept in the pasture of Marandu grass, and a smaller intake was found in the animals kept in the pasture of Massai grass. Intake of leaf blades was higher (p<0.05) in the animals kept in pastures of Massai and Marandu. The neutral detergent fiber intake did not differ among the cultivars. It is concluded that pasture structure and chemical composition of tropical forage cultivars influence the nutrient intake and feeding behavior of sheep. The low leaf blade offer of the pasture of the Aruana grass negatively affects the feeding behavior of the sheep, but the crude protein in forage of this cultivar favors the nutrient intake, feed conversion, and performance of sheep.